Vibrant soundbridge implantation prior to auricular reconstruction with unilateral microtia‐atresia. Issue 8 (16th August 2021) - Yoshimura, Hidekane; Takahashi, Masahiro; Iwasaki, Satoshi; Shinagawa, Jun; Takashimizu, Ikkei; Nagai, Fumio; Yotsuyanagi, Takatoshi; Usami, Shin‐ichi
Abstract: We presented the first successful application of VSB implantation prior to auriculoplasty, which can provide hearing improvement in safe conditions and open new strategies for earlier hearing rehabilitation in unilateral microtia‐atresia children. Abstract : We presented the first successful application of VSB implantation prior to auriculoplasty, which can provide hearing improvement in safe conditions and open new strategies for earlier hearing rehabilitation in unilateral microtia‐atresia children.